Recommendations for designing information security framework in government procurement of goods/services certification systems based on ISO 27001:2022 - Ade Wahyu Kurniawan; Muhammad Salman (Universitas Wiralodra, 2023)
Certification Government Procurement of Goods/Services has applied since 2008 and switched to certification-based computers in 2015. However, technology information has raised problems with the security of necessary information fixed, like illegal access and practice jockeying through access remotely against application exam-based computers. To overcome the challenge, a framework Works security comprehensive information is required. In a study, the researcher compares System Certification Quality Management with Standard ISO 27001:2022 and observes Suite implementation certification procurement to develop a framework special can implement in system certification. Analysis results show that LKPP requires framework Work security information on the system certification procurement goods/services government based on the ISO 27001: 2022 standard. The proposed framework aims to facilitate application Certification Procurement by LKPP as institution-maker regulation and implementation system certification procurement.